Influence of Hinduism on Indian Christian theology a critique appropriating panikkarian trinity - Nannu, K. 1978- (New Delhi Christian World Imprints, 2018)
The subaltern methodology has exerted a great impact in the field of current theology and hermeneutics. Its achievements and advantages are so numerous that no one can deny its significance in contemporary theological developments. This book is a critique on Raymond Panikkar's theology of trinity from the subaltern perspective. It analyses to what extent Panikkar is inclined to Brahmanic Hinduism and why he had more propensity towards Hinduism. The work, therefore, characterizes Panikkar's theology as `Hinduized theology' or to be precise as `Brahmanic theology', considering the fact that the questions and aspirations of the majority people in India could not be thoroughly addressed by him. It concludes that Indian Christian theology is really gasping for breath as it is under Brahmanic captivity. Indeed, this book will prove to be a major contribution to the current debate on Indian Christian theology. --
Raimundo Panikkar : a pilgrimage to contemporary theological consciousness -- Trinity and Hindu spirituality : Panikkar's Triadic Synthesis -- Influence of Hinduism on Panikkar's Theology -- A Subaltern Critique on Hindu Hegemonic Theology of Panikkar
Archivierung/Langzeitarchivierung gewährleistet
B
Keywords: Panikkar, Raimon -- 1918-2010; Panikkar, Raimon 1918-2010; Hinduism -- Relations -- Christianity; Christianity and other religions -- Hinduism; Christianity -- India; Christianity and other religions -- Hinduism; Hinduism -- Relations -- Christianity; Theology of religions (Christian theology); Trinity